ACCOUNTING IN ENVIRONMENTAL PROTECTION: WORLD EXPERIENCE AND THE SITUATION IN KYRGYZSTAN - Salyuev A. A.; Butenko I. V. (Vestnik Issyk-Kulʹskogo universiteta, 2025)
The state of accounting in environmental protection activities has become an increasingly important issue in recent years, as attention to environmental aspects and sustainable development is growing. At this stage, the world community has come to understand that without preserving the environment, there will be no economic development of countries. In this regard, this issue has become the main focus of discussions at the global level. At the moment, Kyrgyzstan is striving for its rapid economic development. To achieve this goal, all available resources are used, including natural ones. In these conditions, it is very important not to cause irreparable damage to our nature and ecology. Careful attitude is the key to a healthy population and the future of our country. We have been reminded of this more than once by recent cataclysms, such as mudflows. This article reveals the peculiarity of accounting for environmental protection activities and its features in foreign countries. Thus, accounting in environmental protection activities requires the integration of environmental and economic indicators, which contributes to better accounting and management of environmental risks.